Risk of recurrence and long-term mortality following radical cystectomy for bladder cancer. (4th March 2022) - van Hauen, Matilde Bangsbo; Maibom, Sophia Liff; Thind, Peter Ole; Martin Poulsen, Alicia; Joensen, Ulla Nordström; Røder, Martin Andreas
Abstract: Purpose: To investigate the risk of recurrence and long-term mortality after radical cystectomy (RC) for bladder cancer (BC) at a high-volume tertiary referral center in Denmark over 19 years. Materials and methods: Patients undergoing RC between the 1st of January 2000 to 31st of December 2018 were included. Patient data were manually retrieved from electronic patient files. Follow-up ended 18th of May 2020. Cumulative incidences were used to assess risk of recurrence and mortality using competing risk modelling. Cause-specific Cox regression models were used for multivariable analysis. Results: A total of 1267 patients underwent RC of which 1042 were eligible for analysis. Overall mortality was 40% and 56% after 5 and 10 years, respectively. The cumulative incidence of recurrence and BC specific mortality was high within the first 2 years. Only 3.2% of the patients with recurrence were alive at the end of follow-up. The cumulative incidence of BC mortality after 5 years was 6.7% (95% CI 3.6–9.9) and 10% (95% CI 6.8–14) for patients with ≤ pT1bN0 and pT2N0, respectively. For patients with lymph node positive disease the cumulative incidence of BC mortality after 5 years was 65% (95% CI 58–71). Conclusions: We found a significant risk of recurrence and disease-specific mortality following RC for BC, especially within the first 2 years following surgery. Our data seem comparable to other large cohorts. The chance of long-term survival following recurrence is low and there is a continuous need to improve adjuvant or salvage strategies following RC.